Perceptions of practicing interior designers: motivations that encourage their sustainable design practices - Templeton, Alisa, author; Clemons, Stephanie, advisor; Tremblay, Ken, committee member; Banning, James, committee member (Colorado State University. Libraries, 2011)
This exploratory research developed an understanding of the various perceptions practicing interior designers have of sustainability and sustainable interior design strategies. Various motivations interior designers have for the pursuit of sustainable interior design strategies were also uncovered. Following a phenomenological method, individual interviews were conducted with eleven interior designers living and practicing in the Denver, Colorado region. Purposeful sampling techniques were utilized in order to obtain participants with experience in the phenomenon in question, sustainable interior design strategies. Participants completed short demographic surveys and answered open-ended questions regarding their experiences with sustainability and sustainable interior design strategies. During these interviews, participants' perceptions of and motivations for sustainable interior design were uncovered. Interviews were audio recorded and transcribed. Motivational data were coded using Means End Chain Theory and perceptional data were coded separately. The findings create an understanding of interior designers' perceptions and motivations as well as their future intentions toward sustainable interior design strategies. The manner in which this research complements the existing literature is also discussed, as are several related areas for future study.
Keywords: design; environment; exploratory; interior; phenomenology; sustainable